A REALIST LITERATURE REVIEW OF TRANSITION TO ADULT SERVICES BY YOUNG PEOPLE WITH LIFE-LIMITING CONDITIONS IN IRELAND. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Kerr, Helen; O'Halloran, Peter; Nicholl, Honor; Price, Jayne
Abstract : Background: As a result of improvements in care and treatment more young people with life-limiting conditions are now living beyond childhood, meaning they must make the transition from children's to adult services. The loss of long-standing relationships with providers of children's services combines with poor co-ordination of services to make this a daunting prospect for young people and their families. However, there is little evidence on transition services for young people with life limiting conditions, with few models of good practice in the literature. Aims: The purpose of this review was to determine the factors that promote or hinder the transition to adult services for young adults with life limiting conditions, and identify gaps to be addressed. Methods: A comprehensive search of the literature was undertaken using key terms, of the following databases; MEDLINE and the Cochrane Database of Systematic Reviews. 314 articles were sourced and inclusion and exclusion criteria were applied to highlight the most relevant literature. Results: Studies were reviewed using a realist review approach and three themes emerged from the literature. Barriers and facilitators to the transition process were identified associated with: 1. The patient 2. Parents/carers 3. The organisation. Conclusion: It is unclear from the literature what the specific factors are that promote or hinder the transition process for young adults with life limiting conditions who go through the transition from children's to adult services, therefore, research is required to identify the factors that promote and hinder the transition process in Ireland. This research is currently being carried out by the author as part of Doctoral studies. The three year full time Doctoral study commenced in January 2013 and is funded by the All Ireland Institute of Hospice and Palliative Care.